Pemanfaatan Media Kartu Bergambar Dengan Pendekatan Kooperatif untuk Meningkatkan Hasil Belajar IPAS Materi Bentang Alam Siswa Kelas III - Muhammad Adnan Alfaruqi; Endang Sri Maruti; Vivi Rulviana (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to analyze the effectiveness of using picture card media with a cooperative approach in improving science and social studies (IPAS) learning outcomes on landform materials for third-grade students of SDN 3 Sawoo. The research method used is Classroom Action Research (CAR) with the Kemmis McTaggart model conducted in two cycles, involving 29 third-grade students as research subjects. Data were collected through tests, observations, and documentation, then analyzed using quantitative and qualitative descriptive techniques. The results showed an increase in student learning outcomes after the application of picture card media with a cooperative approach, with the average score increasing from 56.55 in the pre-cycle to 71.03 in cycle I and 83.79 in cycle II, with learning mastery increasing from 31.00% to 72.41% and 86.21%. The use of picture card media helps students visualize types of landforms, while the cooperative approach encourages active student participation, collaboration, and communication. The Numbered Heads Together (NHT) type was found to be more effective than Think-Pair-Share (TPS) in this context. Therefore, picture card media with a cooperative approach is recommended as an innovative learning strategy to improve the quality of IPAS learning in elementary schools.